2003
DOI: 10.1038/ni883
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling and extragenic transcription at the MHC class II locus control region

Abstract: In vivo, a wild-type pattern of major histocompatibility complex (MHC) class II expression requires a locus control region (LCR). Whereas the role of promoter-proximal MHC class II regulatory sequences is well established, the function of the distal LCR remained obscure. We show here that this LCR is bound by the MHC class II-specific transactivators regulatory factor X (RFX) and class II transactivator (CIITA). Binding of these factors induces long-range histone acetylation, RNA polymerase II recruitment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 44 publications
14
144
0
1
Order By: Relevance
“…Importantly, this activity was CIITA dependent because there was no activity over the background in RJ2.2.5 cells, which lack CIITA. The finding that XL-4 could direct the expression of a reporter gene was similar to that observed previously (14). Therefore, these results suggest that RFX-and CIITA-binding XL boxes could play a role in the regulation of genes in their natural context.…”
Section: Rfx and Ciita-binding XL Boxes Can Drive The Expression Of Asupporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, this activity was CIITA dependent because there was no activity over the background in RJ2.2.5 cells, which lack CIITA. The finding that XL-4 could direct the expression of a reporter gene was similar to that observed previously (14). Therefore, these results suggest that RFX-and CIITA-binding XL boxes could play a role in the regulation of genes in their natural context.…”
Section: Rfx and Ciita-binding XL Boxes Can Drive The Expression Of Asupporting
confidence: 88%
“…Further analyses showed that some of the XL boxes (XL-7 and XL-8) were positioned upstream of ancient duplications bearing homology to the first exon of the HLA-DRB gene (29) and extending several kilobases downstream of exon 1. XL-4, located 2.3 kb upstream of the HLA-DRA gene, was identified previously as a X-Y box region and a potential locus control element (14). Whereas XL-1, -2, and -3 were located further upstream of the HLA-DRA gene, they and XL-5 and -6 were not associated with an identifiable gene fragment.…”
Section: Within the Human Mhcmentioning
confidence: 88%
See 1 more Smart Citation
“…54 A similar SXY motif was found B2.3-kb upstream of the orthologous human HLA-DRA gene 57 and shown to bind RFX and CIITA leading to induction of long-range histone acetylation, recruitment of RNA polymerase II and production of low levels of intergenic transcripts. 58 Several other distal SXY modules acting as transcriptional enhancers have been identified in the MHC class II region. 59 These distal SXY modules add another tier of complexity to class II gene regulation through long-distance control of expression.…”
Section: Sxy-like Sequences and Mhc Class II Gene Regulationmentioning
confidence: 99%
“…For real-time quantitative PCR, 2 μl of the reverse transcription mix was combined with primers for HLA-DRA (Masternak et al, 2003) or beta-actin, and Reaction Mix (QuantiTect SYBR Green PCR kit; Qiagen Inc.). The reactions were carried out in an Opticon 2 real-time thermal cycler (MJ Research Inc., Reno, NV, USA).…”
Section: Quantitative Real-time Reverse Transcriptase Pcrmentioning
confidence: 99%